Bioprinted Constructs that Mimic the Ossification Center Microenvironment for Targeted Innervation in Bone Regeneration. (23rd November 2021) - Li, Wentao; Miao, Weiqiang; Liu, Yihao; Wang, Tianchang; Zhang, Yuxin; Wang, Wenhao; Lu, Dezhi; Zhou, Xianhao; Jiao, Xin; Jia, Xinlin; Lin, Yixuan; Li, Yuchen; et al.
Abstract: Although great progress has been made in engineered bone tissues, delayed or ineffective bone regeneration remains an issue due to the lack of neural network reconstruction in their design. Therefore, an engineered bone tissue construct that mimics the ossification center microenvironment to promote innervation is proposed. Based on this, the NGF@Lap constructs are constructed through bioprinting technology, which can release nerve growth factor (NGF) for a long time and simulate the ossification center's microenvironment with high expression NGF. In vitro, NGF@Lap‐GA can promote axonal extension. Meanwhile, the NGF and Laponite from the constructs can respectively promote the expression and secretion of calcitonin gene‐related peptide (CGRP) in sensory neurons. Further, the constructs show a CGRP‐dependent osteogenic and inhibition of adipogenesis, which is mainly regulated by AMP‐activated protein kinase‐peroxisome proliferator activated receptor pathway. In vivo, the constructs increased neurovascular network density in the tissue surrounding the implant, promoted bone marrow mesenchymal stem cells osteogenic differentiation, and effectively improved bone regeneration in the cranial defect model. In conclusion, the novel tissue‐engineered bone simulates the ossification center microenvironment, promotes innervation, and has promising potential for future application in bone regeneration. Abstract : An NGF@Laponite bio‐printing scaffold simulates the microenvironment of ossification center, which can promote innervation and further promote bone regeneration by regulating nerve‐bone crosstalk. This study highlights the role of the nervous system in bone regeneration and provides a new strategy for using tissue engineering to interfere with the nervous system in bone and thus improve bone regeneration.